1988
DOI: 10.1111/j.1532-5415.1988.tb04263.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Function After Hip Fracture The Role of Social Supports

Abstract: Previous studies have found that social support may reduce mortality after myocardial infarction and reduce overall mortality among the elderly. To determine whether social support also influences the recovery of function among patients who have had hip fractures and to describe other potential predictors of recovery after hip fracture, 111 patients with hip fractures were interviewed and examined before discharge from the hospital. The functional status of surviving patients was assessed again 6 months later.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1
5

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(100 citation statements)
references
References 23 publications
5
89
1
5
Order By: Relevance
“…It is reported that only 43% of patients manage to reach preoperational levels of function 2 months after the operation, while 1 month later, mobility still remains reduced in 20-25% [4,5,10]. Usually, 2 months after the operation none of the patients is in pain, although cases are reported in which, 12-14 months after the operation, 27% of patients still have hip pain [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that only 43% of patients manage to reach preoperational levels of function 2 months after the operation, while 1 month later, mobility still remains reduced in 20-25% [4,5,10]. Usually, 2 months after the operation none of the patients is in pain, although cases are reported in which, 12-14 months after the operation, 27% of patients still have hip pain [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…Greater postfracture muscle strength of the legs (2,7) and arms (8) and more physical therapy sessions (9) are associated with better functional recovery after a hip fracture, which suggests an important role of muscle strength. No studies, however, have investigated the prospective change in muscle strength after a hip fracture and the potential association of this change with functional recovery.…”
mentioning
confidence: 99%
“…Felder-Puig Rosemarie et al had done a study stating that it was necessary for adolescence age group with pathological fractures to deal with problems such as restricted mobility, catching up with school and areas of social wellbeing, their means of emotional support are from older age groups which are often preoccupied with work and daily activities [12].…”
Section: Discussionmentioning
confidence: 99%